Продавец слов - Кивинов Андрей Владимирович (Русский проект, 2004)
Экземпляры: (20240325) / Инвентарный номер: 30196 / Цена: 65.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: К 38 / ГРНТИ: 17 / ББК: 84(2=411.2)6